The Role of Brain-Derived Neurotrophic Factor in Obstructive Sleep Apnea and Endothelial Function in a Pediatric Population With Obesity - Makhout, Sanae; Vermeiren, Eline; Van De Maele, Karolien; Bruyndonckx, Luc; De Winter, Benedicte Y.; Van Hoorenbeeck, Kim; Verhulst, Stijn L.; Van Eyck, Annelies (Frontiers in Medicine, 2022)
BACKGROUND Childhood obesity has increased worldwide, becoming a significant public health concern. Brain-derived neurotrophic factor (BDNF) plays an important role in the central regulation of food intake and body weight, but little is known regarding its role in childhood obesity. Next to obesity, BDNF has been linked to obstructive sleep apnea (OSA) and endothelial dysfunction, two obesity-related comorbidities. The aim of this study is to investigate how BDNF, OSA and endothelial dysfunction interact in children with obesity and to determine the effect of weight loss on serum BDNF levels. METHODS Children and adolescents with obesity aged 8 to 18 years who were enrolled in a multidisciplinary obesity treatment (MOT) in a tertiary hospital, were prospectively included. Several examinations were conducted during this MOT; at baseline, after six months and after 12 months, including the assessment of endothelial function, body composition measurements and a polysomnography. BDNF levels were measured on a serum sample by means of ELISA. RESULTS A total of 103 patients with obesity was included, of which 20 had OSA (19.4%). BDNF levels were comparable in children with obesity and OSA and children with obesity but without OSA (26.75 ng/ml vs 27.87 ng/ml, p=0.6). No correlations were found between BDNF and sleep-related variables or between BDNF and endothelial function parameters nor between BDNF and adiposity measures. To investigate if the interaction between OSA and endothelial dysfunction had an influence on BDNF levels, a general linear model was used. This model revealed that a diagnosis of OSA, as well as the interaction between OSA and maximal endothelial dilatation, contributed significantly (p=0.03, p=0.04 respectively) to BDNF levels. After one year of weight loss therapy, BDNF levels did not change (26.18 ng/ml vs 25.46 ng/ml, p=0.7) in our population. CONCLUSION BDNF concentrations were comparable in children with obesity, both with and without OSA, indicating that BDNF levels are not affected by OSA. However, we did find an interaction effect of OSA and endothelial function on BDNF levels.